Modern treatment methods in atopic dermatitis - literature overview - Martyna Borowska-Łygan; Jakub Tomaszewski; Wojciech Urban; Konrad Strużek; Jan Biłogras; Kornelia Karamus; Rafał Wojciech Rejmak (Journal of Education, Health and Sport)
Introduction and aim: Atopic dermatitis (AD) is a chronic inflammatory skin disease. It is characterised by periods of exacerbation and remission of symptoms such as pruritus, dry skin and eczematous lesions with characteristic morphology. The aim of this study is to present the current state of knowledge on new treatments for atopic dermatitis.